Tuning excited state energy levels by achieving coordination-induced thermally activated delayed fluorescence. Issue 24 (8th November 2022) - Liang, Dong; Jia, Ji-Hui; Cai, Xian-Bao; Zhao, Yu-Qing; Wang, Zhan-Qi; Lu, Can-Zhong
Abstract : In this study, a low steric hindrance D–A type spiro-ligand which possesses long afterglow was used to construct Ag(i ) complexes. The excited states energy level is regulated for resulting in tiny ΔEST and efficient TADF through metal coordination. Abstract : In this study, a low steric hindrance spiro-type diimine ligand, which possesses long afterglow, has been prepared to design Ag(i ) complexes. By achieving coordination-induced thermally activated delayed fluorescence (TADF), the excited state energy level of the spiro-type diamine ligand is regulated, and a small Δ E ST is obtained. Thus, a reverse intersystem crossing (RISC) process is facilitated and an highly efficient TADF is achieved in these Ag(i ) complexes. This mechanism, illustrated in this study, contributes to an in-depth understanding of transformations in different radiative decay pathways.